Evaluation of the Effect of Propolis Nanoparticles on Antimicrobial Properties and Shear Bond Strength of Orthodontic Composite Bonded to Bovine Enamel - Ahmad Sodagar; Azam Akhavan; Sepideh Arab; Abbas Bahador; Maryam Pourhajibagher; Armin Soudi (Tehran University of Medical Sciences, 2019)
Objectives: The present study aimed to investigate the effects of propolis nanoparticles (prpNPs) on antimicrobial property and shear bond strength (SBS) of orthodontic composite bonded to bovine enamel. Materials and Methods: Sixty bovine teeth were randomly divided into five groups (n=12). PrpNPs were prepared at concentrations of 0% (control), 1%, 2%, 5%, and 10% in Transbond XT composite and were used to bond stainless steel brackets to the teeth. A universal testing machine was used to measure the SBS between brackets and teeth. After debonding of brackets, the adhesive remnant index (ARI) on bracket bases was measured. In the microbial test, composites with the aforementioned concentrations of prpNPs were cured in metal discs. The bacteria included Streptococcus mutans (S.mutans), Streptococcus sanguinis (S.sanguinis), and Lactobacillus acidophilus (L.acidophilus), and antimicrobial effects of prpNPs were investigated by anti-biofilm, disc agar diffusion (DAD), and eluted component tests. Results: The group with 10% of prpNPs showed the lowest SBS. The growth of colonies of S.mutans and S.sanguinis at all concentrations (except for 1%) was significantly lower than the control group. The growth of L.acidophilus colonies significantly reduced at 5% and 10% concentrations. Growth inhibition zone was developed at 2%, 5%, and 10% concentrations for S.mutans and S.sanguinis. The lowest numbers of S.mutans and S.sanguinis colonies at all concentrations were observed on the 15th day. L.acidophilus colonies decreased significantly at all concentrations (except for 1%) until the 30th day. Conclusions: Nano propolis has a significant antimicrobial effect at 2% and 5% concentrations, and the ...